AIS based vessel monitoring system using software defined radio - M. Aqsha Aqrizal; Ummul Khair; Ratna Dewi (Journal Geuthee of Engineering and Energy, 2026)
This study implements a low-cost Software Defined Radio (SDR)-based receiver system for the Automatic Identification System (AIS) operating at frequencies of 161.975 MHz and 162.025 MHz using a 44 cm V-dipole antenna with a 90° angle. Spectrum analysis is performed using Airspy to identify AIS signal characteristics in real time within the frequency domain, with measured Signal-to-Noise Ratio (SNR) values of 21.3 dB for AIS 1 and 21.4 dB for AIS 2. The signal decoding process is carried out by AIS-catcher, which handles GMSK demodulation and efficiently extracts AIS message payloads. The decoded data is then visualized using OpenCPN in the form of a digital map to monitor vessel positions and movements in real time. SDRangel is utilized as a supporting platform for signal observation, SDR device configuration, and additional analysis of reception quality. System performance evaluation demonstrates stable capability in receiving and decoding AIS signals with a satisfactory success rate, although it is still affected by interference and propagation conditions. GNU Radio is used in a limited capacity as a signal processing environment for filtering and basic parameter adjustment. The results confirm that low-cost SDR is an effective, flexible, and economical solution for implementing AIS monitoring systems at the research and basic application levels.